Metals in extreme environments; Effect of multiple high velocity shots - Stephenson, John-Joseph (Cranfield University, 2022)
During high strain rate scenarios such as an impact event, a compressive shock wave will propagate through the material. When this wave reaches a free surface, it will be reflected as a rarefaction wave. Interaction of these rarefaction waves can lead to localised tension developing in the material, leading to tensile failure, or spallation, which has been studied extensively over many years.What has been far less studied is the effect of a secondary compression on shock damaged material. This research will investigate this and determine if, and if so under what conditions, recompaction will occur in Aluminium and Titanium. This should provide fundamental knowledge of complex loading scenarios, aiding understanding of extreme events in both civil and military spheres. The work will involve the design of a passive' recovery system, which in addition to reducing the time required to produce samples for this work will have wider applications within the shock community.During high strain rate scenarios such as an impact event, a compressive shock wave will propagate through the material. When this wave reaches a free surface, it will be reflected as a rarefaction wave. Interaction of these rarefaction waves can lead to localised tension developing in the material, leading to tensile failure, or spallation, which has been studied extensively over many years. What has been far less studied is the effect of a secondary compression on shock damaged material. This research will investigate this and determine if, and if so under what conditions, recompaction will occur in Aluminium and Titanium. This should provide fundamental knowledge of complex loading scenarios, aiding understanding of extreme events in both civil and military spheres. The work will involve the design of a 'passive' recovery system, which in addition to reducing the time required to produce samples for this work will have wider applications within the shock community.
Keywords: Shock waves; Spall; Recovery; DSDS2022; DSDS2022 3MT